11x+5+6x=

Simple and best practice solution for 11x+5+6x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+5+6x= equation:


Simplifying
11x + 5 + 6x = 0

Reorder the terms:
5 + 11x + 6x = 0

Combine like terms: 11x + 6x = 17x
5 + 17x = 0

Solving
5 + 17x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 17x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + 17x = 0 + -5
17x = 0 + -5

Combine like terms: 0 + -5 = -5
17x = -5

Divide each side by '17'.
x = -0.2941176471

Simplifying
x = -0.2941176471

See similar equations:

| 400000=101300*9.82*x | | -4(3x+6)=15 | | 8x=4x-14 | | 5+5*7= | | 5x+35=12x-36 | | -2x-2(x-9)=-30 | | 3x+x+10= | | 49-2x=7x | | 14x-8=x+19+8x+7 | | -x+y=-6 | | (5)/(6)*8+(3)/(4)=(11)/(12) | | 7x-15=7x+5 | | 10-8x=102-36x | | 13x-12=x+17+7x | | m+(15)=31 | | 3x+6=x+2+4x-7 | | 9x+1=10x-10+9x-7 | | 6x+7=5x-9 | | 3x-1=5+x+3 | | 5x+2=x+1+3x+4 | | 3x+3=4x-3+4 | | 8=2x+2+16x-12 | | Qs=4p-12 | | 13x-9=7x+5x+6 | | 13x-9=8x+5x+6 | | 3(5x-2)-6=3(3x+2) | | 6(m+4)+7(m+6)= | | 0.6(10x-8)-0.2(5x-4)=6 | | 17x+13=10x+20 | | 4n-6n=2 | | 8x^2-x-7=0 | | 3x^3-2x+3x-2=0 |

Equations solver categories